An Analysis of Mathematical Representation Skills in Solving Problems of Systems of Linear Equations in Two Variables - Barti, Novia Permata; Usdiyana, Dian (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Mastering mathematics has been a must in order to face today’s era of globalization. Mathematical representation is one of the skills that must be possessed and developed by students to solve mathematical problems. Solving mathematical problems requires high level of thinking and understanding of mathematical concepts. Low representation skills, however, may be caused by several factors, one of which is that students are not used to dealing with contextual problems frequently encountered in daily basis. The present study aims to determine the types of mathematical representations exhibited by the students along with their tendency of employing particular mathematical representation(s) in solving the problems regarding the system of linear equations in two variables. The descriptive study with qualitative approach was utilized as the method. A total of 22 grade IX F students of state junior high school 10 Tapung were selected as the subject. This study was conducted to investigate the tendency of students’ mathematical representation skills in solving the problems of the system of linear equations in two variables. The results indicate several types of mathematical representations utilized in system of linear equations in two variables, including visual representation of 77%, symbolic representation of 91%, and verbal representation of 27%. In conclusion, the representation skills of the grade IX F students of state junior high school 10 Tapung are still in low category and the students’ tendency in solving the problems of system of linear equations in two variables is to use the symbolic representation